FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LABA PADA PERUSAHAAN PUBLIK MANUFAKTUR - HELINA HELINA; MEIRYANANDA PERMANASARI (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to analyze the factors that influence earnings quality in manufacturing companies. These factors are investment decision, firm perfomance, accounting conservation, firm size, cash holding, financing, and current ratio.The population of this research is manufacturing companies listed in the Indonesia Stock Exchange from 2013-2015. Samples consist of 37 manufacturing companies, selected using purposive sampling method. The data type is secondary data which collected from IDX website. The hypothesis tested using multiple linear regression.The result of this research shows that firm size and cash holding have influences towards earnings quality. While, investment decision, firm perfomance, accounting conservation, financing and current ratio do not have influences towards earnings quality.